In search of our mothers' gardens : womanist prose - Walker, Alice (San Diego : Harcourt Brace, 1983)
Collects the nonfiction writings of the author of "The Color Purple."
Young Adult
Young Adult
Wilson's Public Library
Notable/Best Books (A.L.A.)
Booklist
1160L
Keywords: Authors, American -- 20th century -- Biography; Feminism -- Addresses, essays, lectures; African American women; Walker, Alice, -- 1944-; Walker, Alice, -- 1944; American authors -- Biography; Feminism -- Addresses and essays; African American women